2016
DOI: 10.1371/journal.pone.0165794
|View full text |Cite
|
Sign up to set email alerts
|

Voxel-Based Sensitivity of Flat-Panel CT for the Detection of Intracranial Hemorrhage: Comparison to Multi-Detector CT

Abstract: ObjectivesFlat-panel CT (FPCT) allows cross-sectional parenchymal, vascular and perfusion imaging within the angiography suite, which could greatly facilitate acute stroke management. We hypothesized that FPCT offers equal diagnostic accuracy compared to multi-detector CT (MDCT) as a primary tool to exclude intracranial hemorrhage.Methods22 patients with intracranial hematomas who had both MDCT and FPCT performed within 24 hours were retrospectively identified. Patients with visible change in hematoma size or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…13 However, the pre-MT ASPECTS can be very important for the treating neurointerventionalist in patients with wake-up strokes or unknown clinical onset as well as in scenarios in which intervention is prolonged and termination of the MT has to be discussed after multiple thrombectomy maneuvers. There is growing evidence that FDCT can be reliably used to exclude intracerebral hemorrhage 9,14,15 and that the use of timeresolved flat detector CTA and flat detector CTP is feasible, showing sufficient reliability for decision-making. 16,17 One of the most recent studies addressing the reliability of FDCT in acute stroke by Eckert et al 15 also reported data on the reliability of detecting ischemic changes on FDCT.…”
Section: Discussionmentioning
confidence: 99%
“…13 However, the pre-MT ASPECTS can be very important for the treating neurointerventionalist in patients with wake-up strokes or unknown clinical onset as well as in scenarios in which intervention is prolonged and termination of the MT has to be discussed after multiple thrombectomy maneuvers. There is growing evidence that FDCT can be reliably used to exclude intracerebral hemorrhage 9,14,15 and that the use of timeresolved flat detector CTA and flat detector CTP is feasible, showing sufficient reliability for decision-making. 16,17 One of the most recent studies addressing the reliability of FDCT in acute stroke by Eckert et al 15 also reported data on the reliability of detecting ischemic changes on FDCT.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, FDCT was used mainly in assessing acute periprocedural or postprocedural complications in the angiography suite 7 8. With the new generation of FDCT, the diagnostic accuracy for early ischemic lesions or intracranial hemorrhage is comparable to that of MDCT 5 9–11. This has potential implications for clinical workflows when acute stroke is suspected—‘one-stop shopping concept’12 13—as well as in predicting treatment outcomes and in decision making in the acute stroke setting in the angiography suite 14…”
Section: Discussionmentioning
confidence: 99%
“…In the past, inaccurate detection of intracranial hemorrhage was the biggest hurdle in using FDCT for stroke diagnosis 21 22 . This situation seems to be improved when FDCT is performed with the latest generation of angiography systems 23 . Leyhe et al reported not only high sensitivity and specificity for the detection of intracranial hemorrhage, but also demonstrated the feasibility of gray-white differentiation in the supratentorial region with the latest generation of FDCT 24 .…”
Section: Discussionmentioning
confidence: 99%